2018
DOI: 10.17576/pengurusan-2018-53-03
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Risk Management Practices in Information Systems Project in the Public Sector

Abstract: Risk has been identified as one of the important factors that influences the success of Information Systems projects.Poor risk management could pose a threat to project performance and outcome. Many risk management models and standards have been developed to assist project managers and teams to overcome or minimize the impact of project risk. Despite continuous attention and emphasis on the positive contributions of risk management to a project, risk management practices are relatively lacking and it have not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The purpose of risk assessment is to identify potential threats to the success of an activity, system, or project and to evaluate the likelihood and consequences of these threats. The results of the risk assessment can be used to develop risk-mitigation strategies that can help reduce risks and improve the overall safety and reliability of an activity, system, or project [29]- [32]. As shown in Figure 2 and 3, risk assessments typically involve several steps, including (a) hazard identification, identifying potential hazards and risks associated with the activity, system, or project; (b) risk evaluation, evaluating the likelihood and consequences of each identified hazard; (c) risk prioritization, prioritizing the risks based on the likelihood and consequences of each risk; (d) risk mitigation, developing, and implementing strategies to reduce the risks associated with the identified hazards; and (e) monitoring and review, monitoring, and reviewing the risk assessment to ensure that the identified risks are being effectively managed and mitigated [33].…”
Section: Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of risk assessment is to identify potential threats to the success of an activity, system, or project and to evaluate the likelihood and consequences of these threats. The results of the risk assessment can be used to develop risk-mitigation strategies that can help reduce risks and improve the overall safety and reliability of an activity, system, or project [29]- [32]. As shown in Figure 2 and 3, risk assessments typically involve several steps, including (a) hazard identification, identifying potential hazards and risks associated with the activity, system, or project; (b) risk evaluation, evaluating the likelihood and consequences of each identified hazard; (c) risk prioritization, prioritizing the risks based on the likelihood and consequences of each risk; (d) risk mitigation, developing, and implementing strategies to reduce the risks associated with the identified hazards; and (e) monitoring and review, monitoring, and reviewing the risk assessment to ensure that the identified risks are being effectively managed and mitigated [33].…”
Section: Risk Assessmentmentioning
confidence: 99%
“…The level of detail and complexity of a risk assessment will depend on the nature of the activity, system, or project being assessed as well as the goals and objectives of the assessment. However, the overall aim of risk assessment is to identify and manage risks to ensure the safe and reliable operation of the activity, system, or project being assessed [32], [35]- [36]. Conducting a risk assessment for FSPV systems requires tools to identify potential hazards, evaluate the likelihood and consequences of each hazard, and develop effective mitigation strategies, as shown in Figure 4 [37], [38]- [43].…”
Section: Risk Assessmentmentioning
confidence: 99%
“…Most project managers do perform a risk assessment and risk control but fail to come up with a proper risk management plan (Reed and Angolia, 2018). Despite continuous attention and emphasis on the positive contributions of risk management to a project, risk management practices are relatively lacking, and they have not been practiced holistically in the Malaysian ICT sector (Baharuddin and Yusof, 2018). One of the key factors that contribute to the inefficient management of risk in ICT projects in Malaysia is due the culture of the organization itself.…”
Section: Cost Influencing Factors During Project Initialization and P...mentioning
confidence: 99%
“…Based on Taherdoost and Keshavarzsaleh (2016), ICT projects are more vulnerable to risk due to their agility, high technology, and complex nature of projects. Studies done by Baharuddin and Yusof (2018) reveal that there is a lack of risk management emphasis in ICT projects, firstly due to the culture, where the risk management importance is not cascaded down effectively to the project team. This finding is consistent with the findings from other scholars, Altuntus et al (2011).…”
Section: Cost Influencing Factors During the Project Execution Phasementioning
confidence: 99%